Issues pertaining to Mg, Zn and Cu in the 2020 Dietary Reference Intakes for Koreans - Chung, Hae-Yun; Lee, Mi-Kyung; Kim, Wookyoung; Choi, Mi-Kyeong; Kim, Se-Hong; Kim, Eunmee; Kim, Mi-Hyun; Ha, Jung-Heun; Lee, Hongmie; Bae, Yun-Jung; Kwun, In-Sook (Nutrition research and practice, 2022)
In the current years, it has now become necessary to establish standards for micronutrient intake based on scientific evidence. This review discusses issues related to the development of the 2020 Dietary Reference Intakes for Koreans (KDRI) for magnesium (Mg), zinc (Zn), and copper (Cu), and future research directions. Following issues were encountered when establishing the KDRI for these minerals. First, characteristics of Korean subjects need to be applied to estimate nutrient requirements. When calculating the estimated average requirement (EAR), the KDRI used the results of balance studies for Mg absorption and factorial analysis for Zn, which is defined as the minimum amount to offset endogenous losses for Zn and Mg. For Cu, a combination of indicators, such as depletion/repletion studies, were applied, wherein all reference values were based on data obtained from other countries. Second, there was a limitation in that it was difficult to determine whether reference values of Mg, Zn, and Cu intakes in the 2020 KDRI were achievable. This might be due to the lack of representative previous studies on intakes of these nutrients, and an insufficient database for Mg, Zn, and Cu contents in foods. This lack of database for mineral content in food poses a problem when evaluating the appropriateness of intake. Third, data was insufficient to assess the adequacy of Mg, Zn, and Cu intakes from supplements when calculating reference values, considering the rise in both demand and intake of mineral supplements. Mg is more likely to be consumed as a multi-nutrient supplement in combination with other minerals than as a single supplement. Moreover, Zn-Cu interactions in the body need to be considered when determining the reference intake values of Zn and Cu. It is recommended to discuss these issues present in the 2020 KDRI development for Mg, Zn, and Cu intakes in a systematic way, and to find relevant solutions.